The study of compounds distilled with water vapor of Populus laurifolia Ledeb. leaves - A. M. Rudnyk (The State Expert Center of the Ministry of Health of Ukraine, 2021)
Poplar plants (Populus L.) are one of the promising species for inclusion in the State Pharmacopoeia of Ukraine. To date, extensive experience has been accumulated in the use of extracts from buds, leaves and bark of various types of poplars in folk and official medicine as effective anti-inflammatory, antipyretic, analgetic, antibacterial agents. According to literature data only buds are pharmacopoeial raw materials in some countries of the world. Poplar leaves are of interest as a new promising type of medicinal plant raw material, since they have a chemical composition close to the buds, moreover, they are much easier to harvest and the possible volume of raw materials procurement is much larger. The laurel-leaf poplar (Populus laurifolia Ledeb.) is assigned to the section of balsamic poplars (Tacamahaca). It is grown in forest culture, used for landscaping and creation of field-protective plantations in Ukraine. Continuing a comprehensive pharmacognostic study of raw materials of plants of the genus poplar, purpose of this work was to study composition and content of compounds distilled with water vapor of leaves of laurel-leaf poplar cultivated in Ukraine. Leaves for research were harvested in June 2019, from trees growing on the shores of the Murom reservoir in the village of Russkiye Tishki, Kharkiv region (50°09'30"N 36°29'10"E). The composition of compounds distilled in water vapor was investigated on Agilent Technologies 6890N (USA) chromatograph with a 5973N mass spectrometric detector. The total content of compounds distilled with water vapor was 2 126.1 mg/kg. 46 compounds were identified. Terpenoids were presented by 20 compounds with a total content 1 444 mg/kg, the remaining 26 compounds were aromatic substances (256.2 mg/kg) and compounds of various groups (216.8 mg/kg). The dominant compounds in content were β-eudesmol (776.4 mg/kg), γ-eudesmol (298 mg/kg), α-bisabolol (125.9 mg/kg), eugenol (70.9 mg/kg). The data obtained indicate the rich chemical composition of leaves of laurel-leaf poplar and are the basis for further in-depth study of this raw material for assessment the possibility of using it as a medicine.